Mejoramiento de procesos de extracción de minrales en la conpañia minera La Mana ROME-GOLD S.A. - Rivera Chicaiza, César Fernando (2019)
This research project proposes to improve the mineral extraction process that will allow to manage large solutions rich diluted in grams of gold by the zinc precipitation method, which will help in the recovery of the concentrates that enters the hydrometallurgy plant and have a decrease in amounts of metals with high and significant values, which is presented in the adsorption area and that are deposited in the lap, its main product is gold (Au) that recovers at 22 days and as the second product is silver (Au) that is extracted at 4 to 5 months by its low law of concentrate and thus taking advantage of the resources offered by the nature of the Compañía Minera La Maná Roma-Gold S.A. Keyword: Merrill Crowe system, zinc precipitation, head law, tail law, activated charcoal law.